Legal mechanism for the protection of personal data in Germany - Stanislav A. Shadrin, Adel I. Abdullin, (Opción, 2019)
In this regard, this article examines some of the provisions of the new Federal Law of Germany on data protection via general scientific and private scientific methods such as dialectical materialism, systemic, structural-functional, historical, general-logical, formal-legal, comparative-legal. As a result, the German Law on Data Protection has retained a complex internal structure and the new Law poses new problems of interpretation of the European legislation. In conclusion, design under the influence of the practice of the German Constitutional Court is one of the features that are inherent in the legal mechanism for the protection of personal data in Germany.